PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT MAJELIS PENDIDIKAN ACEH - Cut Rizka Safrianti; Faisal Faisal; Sofyan Idris (Jurnal Magister Manajemen, 2018)
The main purposes of this study is to analyze the effect of work environment and transformational leadership style on employee’s job satisfaction and performance of Aceh Education Council Secretariat. The study conducted of 42 employees of the office. The data collected by questionnaire and then the data is analyzed by statistical means of path analysis. The study found that work environment and transformational leadership style positively and significantly effect on employee’s job satisfaction and performance of the institution. The job satisfaction mediates the effect of the two exogenous variable on employee’s performance. The mediating effects of the job satisfaction in mediating the effect of the two variables on employee performance is partial mediation